Hadis tentang Uang: Analisis Syarah terhadap Nilai Uang dalam Perspektif Ekonomi Islam - Muhammad Tsani Abdillah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the understanding of hadith about the value of money in the perspective of Islamic economics. This research applies a qualitative type through literature study using thematic, takhrij, and syarah hadith methods as well as descriptive analysis. The discussion of this research includes an overview of money, thematic hadiths regarding money, and an understanding of the hadith about the value of money from an Islamic economic perspective in the contemporary era. This study concludes that the money used by Muslims at the time of the Prophet was Persian silver dirhams and Roman gold dinars, traditions about money are known to be maqbul traditions and can be used as evidence, and the understanding of hadiths about the value of money is closely related to buying and selling and selling. an effective prohibition of usury for controlling inflation so that people's purchasing power is maintained and economic stability is created, in this case Islamic economics which emphasizes increasing people's welfare is recognized in this contemporary era dealing with money politics with the ideology of capitalism.